X-Linked Hyper IgM Syndrome Manifesting as Recurrent Pneumocystis jirovecii Pneumonia: A Case Report. (10th May 2020) - Huang, Sai Hu; Meng, Xiang Ying; Bai, Zhen Jiang; Li, Ying; Wu, Shui Yan
Abstract: We reported a Chinese boy with X-linked hyper IgM (XHIGM) syndrome, manifesting as recurrent and severe pneumonia caused by Pneumocystis jirovecii . His parents were healthy and unrelated. In August 2018, the 5-month-old boy manifested as cough and dyspnea, and then in July 2019, he was admitted because of the same symptoms. Immunological results of the two admissions both showed low IgG, low IgA, normal IgM and high levels of 1, 3-β-D-glucan (BDG). Using next-generation sequencing (NGS), great reading counts of P. jirovecii were identified from the deep sputum in both admissions. Caspofungin combined with trimethoprim-sulfamethoxazole were used to anti-infection, and he recovered quickly. Whole-exome sequencing was performed for this family because of immune suppression, the disease-causing gene (exon 10–22 of CD40L ) deletion for XHIGM syndrome was identified. NGS is beneficial for etiology diagnosis. P neumocystis jirovecii pneumonia as an opportunistic infection could be recurrent in patients with XHIGM syndrome.